A Closer Look at Young Adult-Parent Relationships: Examining Demand/Withdraw Patterns and Communication Competence. (1st September 2020) - LaFreniere, Jenna R.
Abstract : This study tested young adults' perceptions of their parents' communication competence as a mediating variable in the relationship between their demand/withdraw patterns and closeness with each parent. Participants included 280 young adult children. Bootstrapping analyses revealed that perceptions of each parent's communication competence functioned as an important explanatory mechanism linking the adverse effects of parents and young adults engaging in demand/withdraw interactions and parent-young adult closeness. This finding underscores the significance of healthy relational communication between parents and older children and perceptions of parents' ability to communicate in ways that display clarity, appropriateness, and effectiveness. Implications are provided.